2014
DOI: 10.1155/2014/476430
|View full text |Cite
|
Sign up to set email alerts
|

Hemin Attenuates Cisplatin-Induced Acute Renal Injury in Male Rats

Abstract: Background. The aim of this study is to investigate the protective effects of hemin (the heme oxygenase-1 [OH-1] inducer) against nephrotoxic effects induced by cisplatin [cis-diamminedichloroplatinum II (CP)] in male rats. Methods. The evaluation was performed through monitoring renal redox parameters: lipid peroxidation (LPO), glutathione peroxidase (GPx), superoxide dismutase (SOD), glutathione reductase (GR), and reduced glutathione (GSH). The work also examined renal function tests (urea and creatinine), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…In addition, hemin inhibited the nuclear factor erythroid 2-related factor 2 (Nrf2) activating antioxidant response elements, which regulated genes for many antioxidant enzymes (Al-Kahtani et al 2014). Al-Kahtani et al (2014) have also reported that hemin-mediated increase of HO-1 activity was proved enough to decrease the NO-dependent pathological and infl ammatory conditions that support the obtained results in our study. Cross link exists between HO and NOS systems.…”
supporting
confidence: 88%
“…In addition, hemin inhibited the nuclear factor erythroid 2-related factor 2 (Nrf2) activating antioxidant response elements, which regulated genes for many antioxidant enzymes (Al-Kahtani et al 2014). Al-Kahtani et al (2014) have also reported that hemin-mediated increase of HO-1 activity was proved enough to decrease the NO-dependent pathological and infl ammatory conditions that support the obtained results in our study. Cross link exists between HO and NOS systems.…”
supporting
confidence: 88%
“…GENERATION OF SITE-SPECIFIC TRANSGENIC HO-1 MICE prone to developing AKI (11,23). Several studies have proposed oxidative stress as a major determinant of the pathophysiology during cisplatin injury, and in corroboration, induction of antioxidants, such as HO-1, or supplementation with N-acetyl cysteine before cisplatin administration has led to a favorable response (1,2,4,11,23). We chose to address the effects of HO-1 expression in cisplatin nephrotoxicity for two reasons.…”
Section: F389mentioning
confidence: 99%
“…It has been shown that HO-1 induction ameliorates acute and chronic kidney injury such as ischemia-reperfusion (Chen et al 2015), cisplatin (Al-Kahtani et al 2014), and 5/6 nephrectomy (Desbuards et al 2009). On the other hand, the inhibition of this enzyme was found to aggravate renal damage (Ishikawa et al 2001;Takizawa et al 1998).…”
Section: R a F Tmentioning
confidence: 99%